Preschool Educational Institutions In the Uzbek SSR After the National Division - Y.B.Tursunova (Researchparks Publishing, 2023)
This scientific article describes historical processes related to the history of pre-school educational institutions, which formed the upper level of the educational system that is an integral part of cultural life in the territory of Uzbekistan: the organisation of pre-school educational institutions, the peculiarities of the educational system in them, the issue of financing and the policy of the colonial administration in relation to kindergartens.